KOMPENSASI EKSEKUTIF DAN DIREKTUR PEREMPUAN SEBAGAI DETERMINAN PENGHINDARAN PAJAK PERUSAHAAN - NURFITRIANI NURFITRIANI; FITO CAHYA PUTRA; BINTA ISTIANA AMELVIC; ZAHARA ABELIA LAVENZAD; FILDZAH RASYQANDARIE (Fakultas Ekonomi Universitas Islam Indragiri, 2025)
This study examines the effect of executive compensation and the presence of women directors on corporate tax avoidance in companies listed in the Basic Materials sector on the Indonesia Stock Exchange during 2022–2024. A sample of 43 companies with observations 129 firm was analyzed using panel data regression. The results indicate that executive compensation tends to increase tax avoidance, whereas the presence of women directors significantly reduces it. Firm profitability strengthens tax avoidance, while larger firms tend to be more compliant. These findings highlight the contrasting but complementary roles of managerial incentives and board gender diversity in shaping corporate tax behavior. The study contributes theoretically to corporate governance and taxation literature and offers practical insights for policymakers and firms aiming to enhance tax compliance and ethical governance practices